The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1016/s0014-5793(02)02275-5
|View full text |Cite
|
Sign up to set email alerts
|

A novel rat hypothalamic RFamide‐related peptide identified by immunoaffinity chromatography and mass spectrometry

Abstract: Recently, cDNAs encoding novel RFamide-related peptides (RFRPs) have been reported in the mammalian brains by a gene database search and the deduced RFRPs have been suggested to participate in neuroendocrine and pain mechanisms in the rat. Two peptides have been predicted to be encoded in the cDNA of rodent RFRPs. To assess precise functions of rodent RFRPs in the brain, in the present study we identified a naturally occurring RFRP in the rat hypothalamus by immunoaffinity purification combined with mass spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
118
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 169 publications
(122 citation statements)
references
References 21 publications
4
118
0
Order By: Relevance
“…We were not only able to observe GnIH immunoreactive (ir) cell bodies, but also dense RFRP-3-ir fiber networks in regions known to regulate both reproductive hormones and behavior, confirming other reports in the male rat (Hinuma et al, 1998). We therefore set out to test the hypotheses that central administration of rat RFRP-3 (Ukena et al, 2002) would have inhibitory effects on gonadotropin secretion-as seen in other species with GnIH-and on sexual behavior in the adult male rat. Our data indicates that RFRP-3 is present in the rat hypothalamus and it stimulates GH secretion but is an inhibitor of both LH secretion and sex behavior; and, RFRP-3 has no effect on FSH in the male rat.…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…We were not only able to observe GnIH immunoreactive (ir) cell bodies, but also dense RFRP-3-ir fiber networks in regions known to regulate both reproductive hormones and behavior, confirming other reports in the male rat (Hinuma et al, 1998). We therefore set out to test the hypotheses that central administration of rat RFRP-3 (Ukena et al, 2002) would have inhibitory effects on gonadotropin secretion-as seen in other species with GnIH-and on sexual behavior in the adult male rat. Our data indicates that RFRP-3 is present in the rat hypothalamus and it stimulates GH secretion but is an inhibitor of both LH secretion and sex behavior; and, RFRP-3 has no effect on FSH in the male rat.…”
Section: Introductionsupporting
confidence: 85%
“…Furthermore, double-label immunocytochemistry (ICC) revealed a high probability that GnIH terminals were in close contact with GnRH neurons and fibers (Bentley et al, 2003). Recently, another members of this family (RFRP-1 & RFRP-3) were isolated and sequenced in the rat and found to be widely expressed in the rat hypothalamus (Hinuma, Shintani, Fukusumi, Iijima, Matsumoto, Hosoya, Fujii, Watanabe, Kikuchi, Terao, Yano, Yamamoto, Kawamata, Habata, Asada, Kitada, Kurokawa, Onda, Nishimura, Tanaka, Ibata, and Fujino, 2000;Ukena, Iwakoshi, Minakata, and Tsutsui, 2002;Yano, Iijima, Kakihara, Hinuma, Tanaka, and Ibata, 2003). Although structurally similar peptides, the gene sequence encoding avian GnIH is missing in the homologous mammalian gene (Hinuma, Habata, Fujii, Kawamata, Hosoya, Fukusumi, Kitada, Masuo, Asano, Matsumoto, Sekiguchi, Kurokawa, Nishimura, Onda, and Fujino, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…RFamide-related peptides (RFRPs) homologous to GnIH as well as its receptor have been identified previously in rats and mice (38,44,45). As with the Syrian hamster fragment identified in the present study, the rat and mouse prepro-RFRP polypeptide encodes two RFRPs, called RFRP-1 and RFRP-3, with these precursor polypeptides sharing Ϸ80% homology among all three species (Fig.…”
Section: Figsupporting
confidence: 64%
“…In addition to avian species, GnIH-like molecules have been identified in hamsters, rats, and mice (Kriegsfeld et al 2006) wherein GnIH-ir cell bodies were found to be clustered in the mediobasal hypothalamus with pronounced projections and terminals throughout the central nervous system. RFamide-related peptides (RFRPs) homologous to GnIH and its receptors have previously been identified in rats and mice (Hinuma et al 2000, Ukena et al 2002. The extensive distribution of GnIH-ir fibers in the multiple brain areas is consistent with multiple functions of GnIH such as feeding behavior in chickens (Tachibana et al 2005) and sexual behavior in white-crowned sparrows .…”
Section: Introductionmentioning
confidence: 76%